Transradial Intravascular Ultrasound Guided Culotte Stenting with Zotarolimus Eluting Coronary Stents in Renal Artery Bifurcation Stenosis. (2015) - Ruzsa, Z.; Hüttl, K.; Merkely, B.
Abstract : Introduction: Invasive treatment of a renal artery bifurcation stenosis is technically challenging as the stent may occlude a renal artery side branch. Treatment of a patient by transradial intravascular ultrasound (IVUS) guided renal artery stenting is reported. Report: Renal artery stenosis was confirmed by digital subtraction angiography. The renal artery bifurcation stenosis was stented with two balloon expandable zotarolimus eluting stents using the culotte technique and the result was optimized with the kissing balloon technique. Post-interventional IVUS confirmed good stent expansion and apposition after final high pressure balloon angioplasty. Conclusion: Transradial IVUS guided renal artery stenting using the culotte stent technique is an effective procedure to treat complex renal artery bifurcation stenosis.